(untitled) (Journal of the College of Basic Education, 2025)
The study was conducted in the Microbiology Laboratory of the Department of Science, College of Basic Education, Al-Mustansiriya University. The fruiting bodies of the edible oyster mushroom Pleurotus ostreatus (PO) were obtained from the Department of Crop Protection - Department of Organic Agriculture - Baghdad, Iraq. The fruiting bodies were cleaned and dried in a thermal oven at (40-45°C) and stored until use. The peach fruits (Prunus persica) were obtained from the local markets in Baghdad. They were ripe, of similar size and color, homogeneous, free from mechanical damage and not damaged by microorganisms. They were washed and dried with a piece of cloth and then stored at a temperature of (20-25°C) and a humidity of 65% for 20 days, after dividing them into four groups. The first group (T0) was left untreated as a control group and the other three groups (T1, T2, T3) were immersed in concentrations (1%, 2%, 3%) of chitosan solution extracted from the mushroom Pleurotus ostreatus (PO) for 20 days. (1.5 to 2) minutes respectively. The study showed that immersing the fruits in a 3% chitosan solution gave the best results in maintaining the quality of the fruits in terms of the percentage of fruit weight loss, which amounted to (400, 393, 385 and 377) gm. The 2% concentration proved its worth in increasing the firmness of the fruits (18.6, 17.2, 13.1 and 11.3 N) and the concentration of total solids (TSS) which reached (16.9, 16.6, 15.9, 15.0 and 14.8 Brix) and the content of beta-carotene (5.68, 5.61, 5.55, 5.51 and 5.50 μg/g) and ascorbic acid (6.6, 6.4, 6.3, 6.2 and 6.00 mg/kg). No significant difference was recorded for the two treatments T2 and T3 in measuring the titratable acidity. Chitosan can be used as an environmentally friendly coating to reduce post-harvest losses and extend the shelf life of fruits. Chitosan is considered a promising method to extend the storage period of fruits such as peaches, while maintaining quality.